Suitability of Seagrass Ecosystem for Marine Ecotourism in Padang City, West Sumatera Province - Try Al Tanto; Aprizon Putra; Dedi Hermon; Harfiandri Damanhuri (Universitas Muhammadiyah Surakarta, 2018)
Seagrass ecosystems are exciting parts of the tropical coastal region that are potential for ecotourism activities. Marine ecotourism sector in the city of Padang has begun to develop within last few years. This development has not only positive impacts but also negative threats to the environment. Therefore, carefully select the most suitable areas for this purpose is important. This article aims to propose the potential areas for seagrass ecotourism in Padang city based on Geographic information system (GIS) analysis. We used spatial analysis to develop the seagrass ecotourism suitability index that is also potentially applicable to other areas. The results of the analysis show that area of the seagrass ecosystem in Nirwana beach (23.75 ha), Cindakir beach (2.56 ha), and Pasumpahan island (5.46 ha) with a total area of the seagrass ecosystem overall in Padang City (31.78 ha). These areas have been overgrown by Thalassia hemprichii with coverage 50 – 75 % in Nirwana beach, 25 – 50 % in Cindakir beach and Pasumpahan Island. The suitable areas for seagrass ecotourism were found on the beach of Nirwana (covers 84% as very suitable), Cindakir beach (covers 73 % as moderately suitable) and Pasumpahan island (covers 78 % as moderately suitable). We found that activities of local communities decreased the suitability of Cindakir beach and Pasumpahan island because these activities increase the abundance of mud in the substrate of waters.